Aromanians of Romania and their language - Klimkowski, Tomasz (Balcanica Posnaniensia. Acta et studia, 2012)
Until 1913, all Aromanians lived in the same state i.e. the Ottoman Empire, on equal terms with the other non-Muslim subjects of the sultan. After the Balkan wars, they did not succeed in forming their own state and they became separated by the new borders of the four countries: Greece, Bulgaria, Serbia and Albania. That quickly led to ethnic and linguistic tensions, especially in Greece, which continued its policy of forced assimilation of the Vlachs. The mass emigration to Romania, considered by many Vlachs as their only real homeland – first to the Southern and then to the Northern Dobruja – saved them from persecutions but did not protect their ethnic, linguistic and cultural distinctness from assimilation. After having settled in Romania, Aromanians adopted the Romanian identity and language according to the theory that they represented a part of the Romanian nation and their language – a dialect of Romanian. This traditional, pro-Romanian point of view was the only and official one for a half century, until the late 1970s. It still subsists but competes now with a new, opposite point of view, considered and named a “separatist” one. This new point of view envisages the Aromanians to be a separate nation with a distinct language and requires their recognition as a minority group on behalf of the Romanian authorities. Regarding the linguistic aspect, the Aromanian language used in Romania is strongly influenced by Romanian, both lexically and gramatically. For the Aromanian language, Romanian represents a source of modern life or abstract vocabulary and a model of morphosyntactic structures. As for the linguistic analysis in our present study, it is based on Aromanian-language articles and literary works, translated or original, written by Aromanian intellectuals from Romania (some of whom subsequently having emigrated in the meantime and lived in other countries).